The experimental substantiation of the treatment of transverse (central) acetabular fracture with femoral head subluxation by transosseousosteosynthesis method - V. I. Shevtsov; Yu. M. Irianov; T. A. Silantiyeva; S. Yu. Kochetkov (Бюллетень сибирской медицины, 2008)
The aim of this work was to study the roentgen-and-morphological dynamics of reparative regeneration for the experimental substantiation of treating a transverse (central) acetabular fracture with femoral head subluxation by the method of transosseous osteosynthesis. Experiments were performed using 11 mongrel dogs, both males and females. It has been established that after setting a femoral head into the acetabulum, precise reposition and fixation of its fragments the bone union in the fracture site is achieved within 35—65 days.